The Effect of Instagram Social Media Marketing on Purchase Decisions at Kopi Kenangan - Alya Salsabila; Budi Astuti (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The growth of social media provides opportunities for businesses to make marketing tools. Social media marketing makes it easy for businesses to interact with consumers. Instagram is a social media that can be used as a marketing tool. This study aims to determine the effect of Instagram social media marketing on purchasing decisions. The population that will be used is Indonesian people who have bought and know about Kopi Kenangan products through Instagram. The number of respondents in this study were 210 samples. The sampling technique used purposive sampling method. The analysis tool in this study is SEM with PLS version 3.2.9. The results showed that all hypotheses were accepted. Social media marketing, brand equity, and brand awareness have a positive and significant effect on purchase decisions. Social media marketing has a positive effect on brand equity and brand awareness. Social media marketing has a positive and significant effect on purchase decisions through brand awareness.